Seroprevalence of SARS-CoV-2 antibodies among healthy blood donors in Karachi, Pakistan - Younas, Amber (Transfus Apher Sci, 2020)
BACKGROUND: Covid-19 spread through blood transfusion has not yet been reported. Despite the prevailing pandemic, there are no recommendations available as yet for testing SARS-CoV-2 antibodies as part of blood screening. OBJECTIVE: To determine the seroprevalence of SAR-CoV-2 antibodies, its clinical significance and to identify if total antibodies(IgA, IgM, IgG) should be tested or just the specific IgG antibodies only. METHOD: Consecutive blood donors donated were screened for standard serological panel of HbsAg, Anti-HCV, Anti-HIV and Syphilis using Cobas-411 analyser and Malaria. All seronegative donors were then screened for COVID serology using the same instrument. These results were compared with the blood donors’ seroprevalence checked in a cohort in the first week of June 2020. Pre-COVID-19 period (October 2019) blood donors’ archived samples were also compared. Donors who were positive on ECLIA were then tested for specific antibodies (IgM or IgG) by ELISA. RESULTS: A total of 380 healthy blood donors were included. All were males with the mean age being 30.6 ± 6.3 years. Ten pre-pandemic samples did not show COVID-19 antibodies, whereas out of 70 samples in the 3rd week of June, only 15 (21.4 %) were positive. However, in July out of the 300 blood donors, 113 (37.7 %) were found to be reactive. To reconfirm our findings, these 113 donors were then tested on ELISA for presence of IgG specifically. Out of these 128 samples, 81 were IgG positive, 23 were borderline positive and 24 were negative. CONCLUSION: Almost 40 % of blood donors are now seroconverted for COVID-19. This is a reflection of widespread seroprevalence in the adult male population.